Use of technology, job characteristics and work outcomes: a case of UNITAR instructors - Juhdi, Nurita; Abu Samah, Ainon Jauhariah; Saad, Hanita Sarah (World Business Institutes, 2007)
Fifty-two UNITAR instructors were involved in the survey by responding to questionnaires that were personally administered by the researchers. The university implements learning method that blends both e-learning and conventional methods. However, the use of technology among the academic staff varies. The purpose of the study is to measure the relationship between job characteristics and work outcomes; internal motivation, job satisfaction and perceived work effectiveness and to measure to what extent the different level of technology use influences all these variables. The questionnaire was developed based on the Job Diagnostic Survey (JDS) instruments. Discussion and recommendation were made based on the survey findings.